The Question of Time and Timelessness - Nandhikkara, Jose; Yadav, Bibhuti S. (Journal of Dharma, 1976)
Dalabhya, Silaka and Pravahana decide to discuss Udgitha in a place suitable for meditation. With Dalabhya’s permission, Silaka formulates a question: What is the ground of Udgitha? Dalabhya responds by saying that the ground of Udgitha is sound, which is grounded in breathing (prana)-breathing in food (anna) - food in water which in turn has svarga (heaven) as its ground. Svarga is the nebulous world where gods, among other things, attain an object just by desiring it, that plane of existence where wishing is having. Honest to the Upanishadic manner of "seeing" through "talking", the persistent Silaka reformulates the question this way: What is the ground of suarga? Dalabhya advises him to stop there, for svarga is a state higher than which there is nothing; it is the limit of the wishes of man insofar as he is a wishing being. Instead of raising questions as to its ground, one should worship svarga.